The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21577/0103-5053.20180014
|View full text |Cite
|
Sign up to set email alerts
|

Production of Furan Compounds from Sugarcane Bagasse Using a Catalytic System Containing ZnCl2/HCl or AlCl3/HCl in a Biphasic System

Abstract: In this work, two catalytic systems combining Lewis and Brønsted acids (ZnCl 2 /HCl and AlCl 3 /HCl) were applied in a tetrahydrofuran (THF)/NaCl aq biphasic system to produce furan compounds from plant polysaccharides. The following cellulosic matrices were applied for this purpose: α-cellulose, microcrystalline cellulose and both native and steam-exploded sugarcane bagasse. The AlCl 3 /HCl catalytic system afforded the best yields for α-cellulose conversion to furan compounds (hydrolysis followed by dehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…The experimental matrix and the EL yields (%) are presented in Table . The factors evaluated were temperature ( T : 160–190 °C), time ( t : 20–60 min), and IL quantity (1–10 equiv), and their levels were selected according to previous works. , As can be seen in Table , the highest EL yield (81%) from MCC was achieved when all factors were at the upper level: 190 °C, 60 min, and 10 equiv of [TauIm]­[HSO 4 ] (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental matrix and the EL yields (%) are presented in Table . The factors evaluated were temperature ( T : 160–190 °C), time ( t : 20–60 min), and IL quantity (1–10 equiv), and their levels were selected according to previous works. , As can be seen in Table , the highest EL yield (81%) from MCC was achieved when all factors were at the upper level: 190 °C, 60 min, and 10 equiv of [TauIm]­[HSO 4 ] (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…The maximum yield of furfural and HMF obtained were 720 and 200 g kg –1 , respectively, at 190 °C, 1% H 2 SO 4 , and 10 min . Gomes et al reported the production of furfurals from dehydration of steam exploded sugar cane bagasse using AlCl 3 /HCl. The highest yield of HMF and furfural were 440 and 922 g kg –1 , respectively, at 180 °C .…”
Section: Resultsmentioning
confidence: 99%
“…Gomes et al reported the production of furfurals from dehydration of steam exploded sugar cane bagasse using AlCl 3 /HCl. The highest yield of HMF and furfural were 440 and 922 g kg –1 , respectively, at 180 °C . In this study, the maximum yields of HMF and furfural obtained from pretreatment of sugar cane bagasse using IPEG200 at 120 °C were 460 and 140 g kg –1 , respectively, which is comparable with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In H 2 O/THF biphasic system, Fang et al (2019) obtained 76 and 81% yields of HMF and furfural from corn stover, respectively, using H 2 SO 4 /Na 2 SO 4 as catalyst. In combination of Lewis acid with Brønsted acids in NaCl-H 2 O/THF biphasic system, the yields of HMF and furfural was 44.0 and 92.2% catalyzed by AlCl 3 /HCl and 36.5 and 81.4% by the catalysis of ZnCl 2 /HCl, respectively (Gomes et al, 2018). As high as 71% yield of furfural and 30% yield of HMF could be simultaneously produced from wheat straw in NaCl-H 2 O/THF biphasic system catalyzed by SnCl 2 -PTA/β (Phosphotungstic acid) catalyst (Xu et al, 2019).…”
Section: The Co-production Of Hmf and Furfuralmentioning
confidence: 99%